SECONDARY PREVENTION TO REDUCE THE OCCURRENCE OF RECURRENT STROKE ON ISCHEMIC STROKE - Hidayah Karuniawati; Zullies Ikawati; Abdul Gofir (Faculty of Pharmacy, Universitas Gadjah Mada)
One of the purpose from stroke theraphy is to prevent recurrent stroke using secondary prevention by administering antiplatelet/anticoagulant, antihypertensive, antidyslipidemia, and antihyperglycemic. This study aimed to find the influence of secondary prevention on the occurrence of recurrent stroke and determine the factors that involve in the occurrence of recurrent stroke. This research was conducted with a quantitative approach and retrospective case-control study. The subjects were 165 respondents consisted of 82 respondents in the case group and 83 respondents in the control group. Data were analyzed using bivariate/chi square and logistic regression multivariate test. The result showed that the secondary prevention and patient’s compliance reduced the incident of recurrent stroke. The rate of recurrent stoke was decreased from 68% to 24% by antiplatelet therapy and compliance, from 69% to 23% by antihypertensive and compliance, from 54% to 29% by antidislipidemic and compliance, from 52% to 23% by antihiperglikemic and compliance, and the combination of these four secondary preventions reduced the recurrent stroke from 52% to 13%. Multivariate analysis showed that the several factors involved in determining the rate of recurrent stroke, namely patiens who did not use antihypertensive therapy (P=0,000; OR 9.871), had systolic blood pressure≥140mmHg (P=0,011; OR 3,156), HDL<40mg/dl (P=0,005; OR 3,594), and the lack of exercise (P=0,048; OR 2,365).Keyword: recurrent stroke, secondary prevention, compliance, antihypertensive therapy